Formation of 1, 3‐Diphosphacyclobutadiene Complexes from Phosphaalkynes and Their Coordination Behavior. Issue 10 (22nd November 2013) - Rummel, Eva‐Maria; Eckhardt, Maria; Bodensteiner, Michael; Peresypkina, Eugenia V.; Kremer, Werner; Gröger, Christian; Scheer, Manfred
Abstract: By using [(Cp″′Co)2 tol] (Cp″′ = η 5 ‐C5 H2 t Bu3, tol = toluene), a new synthesis of the 1, 3‐diphosphete complexes [Cp″′Co(η 4 ‐P2 C2 t Bu2 )] (1a ) and [Cp″′Co(η 4 ‐P2 C2 i Pr2 )] (1b ) was found, and their reactions with the Lewis acids W(CO)4 and Cu I halides were investigated. The reaction of1b with W(CO)4 (nbd) (nbd = norbornadiene) leads to the complex [(Cp″′Co)(μ, η 4:1 ‐PC i Pr2 )]2 W(CO)4 (2 ) with the two diphosphete complexes1b coordinated trans to a central W(CO)4 moiety. The reactions of1a with Cu I halides result in different products depending on the stoichiometry. In a 1:1 ratio, the dimeric compounds3a –c [(Cp″′Co)(μ, η 4:1 ‐PC t Bu2 )Cu(μ‐X)]2 (3a : X = Cl;3b : X = Br, 3c : X = I) were isolated, whereas an excess of CuX gave the two‐dimensional polymers [(Cp″′Coμ3, η 4:1:1 ‐(PC t Bu)2 )2 (Cuμ3 ‐X)4 ] n (6a : X = Cl, 6b : X = Br, 6c : X = I). From the reaction of1a and1b with CuBr and CuI in a 1:2 or 2:3 ratio, the one‐dimensional polymers [(Cp″′Coμ3, η 4:1:1 ‐(PCR)2 )(Cp″′Coμ, η 4:1 ‐(PCR)2 )(Cuμ3 ‐X)4 ] n (4a : X = Br, R = i Pr, 4b : X = I, R = i Pr, 4c : X = I, R = t Bu) are formed. From the reaction of1a with CuI, a second product, [(Cp″′Coμ3, η 4:1:1 ‐(PC t Bu)2 )(Cuμ3 ‐I)4 (MeCN)2 ] n (5 ), was isolated by using CH3 CN for crystallization. The products were comprehensively characterized by spectroscopic methods, X‐ray crystallography, and 31 P magic angle spinning (MAS) NMR spectroscopy. Abstract : A new synthetic route to diphosphete complexes of cobalt was developed and their reactivity towards W(CO)4 (nbd) (nbd = norbornadiene) and Cu I halides was investigated. For the latter, dimeric, 1D, or 2D polymeric compounds are obtained depending on the stoichiometry used, and their structures reveal (CuX)4 cubes connected by diphosphete units in which each P atom is able to coordinate to a copper atom.